Anatomical Evaluation of Different Approaches for Tibiotalocalcaneal Arthrodesis. (February 2014) - Rausch, Sascha; Loracher, Clemens; Fröber, Rosemarie; Gueorguiev, Boyko; Wagner, Andreas; Gras, Florian; Simons, Paul; Klos, Kajetan
Background: The transfibular approach is commonly used for tibiotalocalcaneal arthrodesis. However, the medial and the posterolateral approaches are available as alternatives. The present study was performed to assess the effects of the 3 approaches on the neurovascular structures encountered and to quantify the extent of cartilage in the different joint compartments that could be surgically debrided. Methods: This cadaver study was performed in 6 pairs of formalin-fixed legs (mean donor age: 80 years; 4 females, 2 males). For each approach, 4 specimens were selected. The neurovascular structures at risk and the debrided portions of the articular cartilage were compared. Results: Arterial structures were least compromised by the transfibular approach. The posterolateral approach was particularly likely to damage the lateral malleolar branches of the peroneal artery. Venous structures were at risk mainly from the medial approach, which was also the most risk-bearing of the 3 approaches in terms of nerve damage. The proportions of cartilage-debrided joint surfaces of the tibia in the ankle joint, and of the talus and the calcaneus in the subtalar joint, did not differ notably. The proportions of debrided surfaces of the talus in the ankle joint differed notably among the 3 approaches. Conclusions: The medial approach could be a valid alternative to the lateral transfibular approach for tibiotalocalcaneal arthrodesis. Care should be taken, however, to prevent damage to the saphenous nerve and other neurological structures. Clinical Relevance: Access morbidity and feasibility of adequate cartilage debridement are relevant to the clinical outcome of hindfoot arthrodesis.